One-dimensional photonic crystal waveguide based on SOI platform for transverse magnetic polarization-maintaining devices - Kazanskiy, Nikolai Lvovich; Butt, Muhammad Ali (Photonics Letters of Poland, 2020)
In this letter, a TM-polarization C-band pass one-dimensional photonic crystal strip waveguide (1D-PCSW) is presented. The waveguide structure is based on a silicon-on-insulator platform which is easy to realize using standard CMOS technology. The numerical study is conducted via 3D-finite element method (FEM). The transmittance and polarization extinction ratio (PER) is enhanced by optimizing the geometric parameters of the device. As a result, a TM polarized light can travel in the waveguide with ~2 dB loss for all C-band telecommunication wavelength window whereas the TE polarized light suffers a high transmission loss of >30 dB. As a result, a PER of ~28.5 dB can be obtained for the whole C-band wavelengths range. The total length of the proposed device is around 8.4 µm long including 1 µm silicon strip waveguide segment on both ends. Based on our study presented in this paper, several photonic devices can be realized where strict polarization filtering is required. Full Text: PDF References B. Wang, S. Blaize, R.S-Montiel, "Nanoscale plasmonic TM-pass polarizer integrated on silicon photonics", Nanoscale, 11, 20685 (2019). CrossRef D. Dai, J.E. Bowers, "Silicon-based on-chip multiplexing technologies and devices for Peta-bit optical interconnects", Nanophotonics, 3, 283 (2014). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Optical elements based on silicon photonics", Computer Optics, 43, 1079 (2019). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Compact design of a polarization beam splitter based on silicon-on-insulator platform", Laser Physics, 28, 116202 (2018). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "A T-shaped 1 × 8 balanced optical power splitter based on 90° bend asymmetric vertical slot waveguides", Laser Physics, 29, 046207 (2019). CrossRef Q. Wang, S.-T. Ho, "Ultracompact TM-Pass Silicon Nanophotonic Waveguide Polarizer and Design", IEEE Photonics J., 2, 49 (2010). CrossRef C.-H. Chen, L. Pang, C.-H. Tsai, U. Levy, Y. Fainman, "Compact and integrated TM-pass waveguide polarizer", Opt. Express, 13, 5347 (2005). CrossRef S. Yuan, Y. Wang, Q. Huang, J. Xia, J. Yu, "Ultracompact TM-pass/TE-reflected integrated polarizer based on a hybrid plasmonic waveguide for silicon photonics", in 11th International Conference on Group IV Photonics (GFP) (IEEE, 2014), pp. 183-184. CrossRef X. Guan, P. Chen, S. Chen, P. Xu, Y. Shi, D. Dai, "Low-loss ultracompact transverse-magnetic-pass polarizer with a silicon subwavelength grating waveguide", Opt. Lett., 39, 4514 (2014). CrossRef A.E.- S. Abd-Elkader, M.F. O. Hameed, N.F. Areed, H.E.-D. Mostafa, and S.S. Obayya, "Ultracompact AZO-based TE-pass and TM-pass hybrid plasmonic polarizers", J.Opt. Soc. Am. B., 36, 652 (2019). CrossRef J. Li et al., "Photonic Crystal Waveguide Electro-Optic Modulator With a Wide Bandwidth", Journal of Lightwave Technology, 31, 1601-1607 (2013). CrossRef N. Skivesen et al., "Photonic-crystal waveguide biosensor", Optics Express, 15, 3169-3176 (2007). CrossRef S. Lin, J. Hu, L. Kimerling, K. Crozier, "Design of nanoslotted photonic crystal waveguide cavities for single nanoparticle trapping and detection", Optics Letters, 34, 3451-3453 (2009). CrossRef T. Liu, A.R. Zakharian, M. Fallahi, J.V. Moloney, M. Mansuripur, "Design of a compact photonic-crystal-based polarizing beam splitter", IEEE Photonics Technology Letters, 17, 1435-1437 (2005). CrossRef R. K. Sinha, Y. Kalra, "Design of optical waveguide polarizer using photonic band gap", Optics Express, 14, 10790 (2006). CrossRef